Epidemiology of Second Non-breast Primary Cancers among Survivors of Breast Cancer: A Korean Population–Based Study by the SMARTSHIP Group - Kim, Haeyoung; Kim, Su SSan; Lee, Ji Sung; Yoon, Jae Sun; Youn, Hyun Jo; Shin, Hyukjai; Lee, Jeong Eon; Lee, Se Kyung; Chung, Il Yong; Jung, So-Youn; Choi, Young Jin; Cho, Jihyoung; et al. (Cancer research and treatment, 2023)
Purpose This study aimed to evaluate the incidence and prognosis of second non-breast primary cancer (SNBPC) among Korean survivors of breast cancer.Materials and Methods Data from the Korean National Health Insurance Service were searched to identify women who received curative surgery for initial breast cancer (IBC) between 2003 and 2008 (n=64,340). Among them, patients with the following characteristics were excluded: other cancer diagnosis before IBC (n=10,866), radiotherapy before IBC (n=349), absence of data on sex or age (n=371), or male (n=248). Accordingly, data of 52,506 women until December 2017 were analyzed. SNBPC was defined as a newly diagnosed SNBPC that occurred 5 years or more after IBC diagnosis.Results The median follow-up time of all patients was 12.13 years. SNBPC was developed in 3,084 (5.87%) women after a median of 7.61 years following IBC diagnosis. The 10-year incidence of SNBPC was 5.78% (95% confidence interval [CI], 5.56 to 6.00). Higher SNBPC incidence was found in survivors with the following factors: old age at IBC diagnosis, low household income, and receiving combined chemotherapy with endocrine therapy, whereas receiving radiotherapy was related to a lower incidence of SNBPC (hazard ratio, 0.89; p < 0.01). Among the patients with SNBPC, the 5-year survival rate was 62.28% (95% CI, 65.53 to 69.02).Conclusion Approximately 5% of breast cancer survivors developed SNBPC within 10 years after IBC diagnosis. The risk of SNBPC was associated with patient’s age at IBC diagnosis, income level, and a receipt of systemic treatments.